Model Pembelajaran Character Building dan Implikasinya Terhadap Perilaku Mahasiswa - Masrukhin, Agus (Humaniora, 2013)
Character Building Subject is required for students in preparation to face the world outside the campus, workplace, society, peers, and even family. Character Building is a process or efforts done to develop, improve and/or to shape characters, dispositions, psychological nature, morals (manners) of human beings (people) that indicate attitudes and good behaviors. Values and factors that influence the Character Building are spirit, togetherness, and caring. The concept of Character Building which could be obtained in formal institutions (campus), informal institutions (family), and non-formal institutions (courses, student spiritual clubs) has an influence and impact on the character of students, whether intentional or not. Nevertheless, it will not happen if there is no self-consciousness in the student. Good Character Building will also be a benchmark in the workplace. Learning Character Building that students get apparently contributes to the formation of student character, of which influences their behaviors. The effect can be seen from the attitude of students such as honesty, trustworthiness in maintaining trust and job given. Character Building is a subject that imparts the values of good behavior to students; and therefore when they jump into the workplace, there will no longer happen the cases of corruption and fraud resulting from the dishonesty because people like that do not have a good character.